(untitled) (Revista Argentina de Cirugía, 2021)
Pneumatosis intestinalis is a rare condition characterized by the presence of gas in the submucosa or subserosa of the intestinal wall. We report two cases associated with generalized abdominal pain and rebound tenderness. The computed tomography (CT) scans in both cases showed bowel distention, pneumatosis intestinalis and portal venous gas. Both patients underwent emergency surgery which demonstrated bowel necrosis with mesenteric ischemia, consistent with the CT images. Both patients died (one during surgery and the other in the immediate postoperative period).